Ensino do cálculo de probabilidade em genética para o cruzamento dos gametas utilizando o quadro de Punnett e aplicativo - Silva, Maria Doralice da (2023)
The work entitled "Teaching the calculation of probability in Genetics for the crossing of gametes using the Punnett square and application" seeks to investigate the teaching of this topic with students in the 3rd year of high school at the Rio Branco State Public School, located in Porto Velho, capital of Rondônia. The study was developed together with the Postgraduate Program in Science and Mathematics Teaching at the University of Passo Fundo (PPGECM/UPF), in the line of research Information, Communication and Interaction Technologies applied to the teaching of Science and Mathematics. The guiding question that guided the research was: "What are the advantages/disadvantages or potential of using an application aimed at calculating probability, in the crossing of gametes when compared to the traditional method, based on the Punnett square?". In this context, a didactic sequence is developed and applied, consisting of ten meetings, in the format of a Potentially Significant Teaching Unit (UEPS) and having the Theory of Meaningful Learning as a theoretical contribution. The research methodology presents a qualitative approach, of an applied nature. As for its objectives, it is characterized as exploratory and participatory. As data collection instruments, observation, logbooks, transcription of dialogues, photos, videos and use of smartphone applications are used. The application of UEPS, in addition to allowing analyzes and inferring signs of significant learning, also provides reflections on the fact that a conventional class, with the use of support and exposition materials, is still a reality and, despite being criticized, may have its value for the systematization of concepts. However, this methodology cannot and should not be the only one used in the teaching-learning process, lacking approaches that promote cognitive movements aimed at meaningful learning. And that the strategies used, in front of the public that involves students who in contemporary times are connected to technologies, contribute to making the teaching-learning process more efficient and enjoyable. In summary, the results showed that prior knowledge is fundamental for students to learn significantly and, also, the importance of teachers paying attention to the planning of activities based on the students' experiential world, contributing to the construction of knowledge.